Anatomy of the Stem Galls Caused by Cotton Stem Weevil (Pempherulus affinis Faust) in Resistant and Susceptible Cultivars of Cotton - DHARAJOTHI, B. (Cotton Research Journal, 2021)
Cotton stem weevil (Pempherulus affinis) is a pest which affects the stem of the cotton by forming exogenous gall and making the plant to lodge. The anatomical changes occurring in different varieties of cotton due to the infestation by Pempherulus affinis were studied. General reaction of the host after infestation was i) the periderm tissues of the bark was moderately affected and dilated, ii) cortex was modified by tangential expansion to limited extent, iii) secondary phloem underwent maximum changes of necrosis, crushing of tissues, obliteration of sieve elements, fragmentation of fibre bands, distortion of phloem fibres and diffusion of hypertrophy and hyperplasia of the ground tissue. This study exhibited a clear difference between the infestation level in resistant and susceptible varieties of cotton. Nadam, Exotica and Moco possess biochemical and physical modification in response to the weevil infestation to be resistant varieties, whereas LRA, MCU-5, Anjali, Surabhi and Sumangala lack these adaptations.